If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
Y-4 = (2/3)*(x-12) // - (2/3)*(x-12)
Y-((2/3)*(x-12))-4 = 0
(-2/3)*(x-12)+Y-4 = 0
Y-2/3*(x-12)-4 = 0
Y-2/3*(x-12)-4 = 0
Y-2/3*x-4+8 = 0
Y-2/3*x+4 = 0
Y-2/3*x+4 = 0
Y-2/3*x+4 = 0 // - Y+4
-2/3*x = -(Y+4) // : -2/3
x = (-(Y+4))/(-2/3)
x = 3/2*(Y+4)
x = 3/2*(Y+4)
| -4.7+8.6x=29.64 | | -5w-7=-12 | | 9x=6y+3 | | 4t+9=-15 | | 10+1s=98 | | 5m+32=7m+14 | | 0.6(-2.5+0.5y)-0.3y=-1.5 | | 5y^2=3y+4 | | t/4-1=2 | | -7m+12=-23 | | 8x+2-4x=2+3x-4 | | 0.04x-0.02y=-0.1 | | -2z-7=13 | | 165=15m | | 8+1w=49 | | 2y^2+11y-5=0 | | 0.6x-0.3y=-1.5 | | 24=18+2h | | 3+3w=15 | | f(x)=-4.9x^2+117x+42 | | -4d-7=-21 | | 3(-0.2y)+5y=33 | | D=Pgk | | 2x-6y+14z=0 | | 15+1m=28 | | 2x-4yi=4+8i | | G(31)=3x-5 | | D=Pkg | | -4x+2-x=37 | | 7y-13=4y+17 | | 3+1t=10 | | 53x^2-233x+84=0 |